Outcome of combined peribulbar ropivacaine 0.75% block and general anesthesia for retinal detachment surgery: A randomized controlled study - Leão, Pedro; Castro, Diogo; Pacheco, Marcos; Soares, José C.; Afonso, Diana (Egyptian journal of anaesthesia, 2016)
Retinal detachment surgery (RDS) is frequently associated with a high incidence of significant perioperative pain and oculocardiac reflex (OCR) intra-operatively. The peribulbar block has gained wide acceptance in ophthalmic anesthetic practice in the recent times. However, there is little current knowledge regarding its efficacy in RDS. This prospective randomized clinical study evaluated the effect and feasibility of peribulbar block when used in conjunction with general anesthesia on perioperative outcome. 98 patients, ASA II-III, were randomly allocated to one of two groups to receive either peribulbar block in conjunction with general anesthesia (n=49) or general anesthesia alone (n=49). Parameters compared were incidence of OCR, surgical bleeding, duration of surgery, postoperative pain and patient‘s satisfaction. Patients with PB block had a significantly lower incidence of intraoperative OCR (n=4 vs. n=13, p<0.05). It also provided more effective post-operative analgesia with fewer patients requiring rescue analgesia medication (n=19 vs. n=27; p=0.105). Surgical bleeding was more profuse in the general anesthesia group (n=5 vs. n=27, p<0.001), with no cases of bleeding interfering with surgery in the peribulbar group. PB block combined with GA improved significantly operating conditions and lower incidence of OCR. Patients in the block group also had better postoperative analgesia.